Physical activity levels during work, leisure time and transport and its association with obesity in urban slum of Mumbai, India - Kadarkar, Kalpak S.; Tiwari, Shraddha R.; Velhal, Gajanan D.; Giri, Purushottam A. (International Journal Of Community Medicine And Public Health, 2017)
Background: Rapid changes in urbanization and associated mechanization and sedentary jobs increase the level of physical inactivity in the population. Physical inactivity is directly reflected in the growing burden of obesity in the Indian population predominantly in the urban areas. WHO developed STEP wise approach for surveillance of risk factors for non-communicable diseases. This study aimed at assessing prevalence of overweight, generalized obesity, abdominal obesity and physical activity status and find out association between them among urban slum population of Mumbai. Methods:Community based, cross-sectional epidemiological study was carried out in urban slum of Mumbai, India during the period of March 2013 to January 2014 by using WHO STEP wise approach. Total number of 600 participants of age group 25-64 years were interviewed and examined for information regarding physical activity and obesity. Results: About 60% of study participants were physical inactivity during work, leisure time and transport. Physical inactivity increased with increased age and female sex. Prevalence of overweight or obesity (generalized obesity) 41.8% was more than that of abdominal obesity 37.7%. Physical inactivity during work, leisure time and transport was significantly associated with obesity and high waist circumference. Conclusions:Physical inactivity was more so with increasing obesity, women and increasing age. To tackle the epidemic of obesity habitual moderate physical activity is the key. It is necessity of time to create environment for adoption of healthy lifestyle through properly channelled health education and advocacy.